Teaching History with Big Ideas : Cases of Ambitious Teachers. - GRAND/GRADWELL (Rowman & Littlefield Pub. Group, 2010)
In the case studies that make up the bulk of this book, middle and high school history teachers describe the decisions and plans and the problems and possibilities they encountered as they ratcheted up their instruction through the use of big ideas. Framing a teaching unit around a question such as "Why don't we know anything about Africa?" offers both teacher and students the opportunities to explore historical actors, ideas, and events in ways both rich and engaging. Such an approach exemplifies the construct of ambitious teaching, whereby teachers demonstrate their ability to marry their de.